The Needs Analysis for an Educational Physics Game with Scientific Literacy and Ethnoscientific Content - Socrates, Tegar Putra; Afrizon, Renol; Hidayati, Hidayati; Hidayat, Rahmat (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
The advancement of science and technology in the era of the Industrial Revolution 4.0 encourages government regulations in changing all life governance, including education. The independent curriculum is used as a solution to answer the demands of the world of education and to be able to create active and creative learning. In learning Physics in schools, its application is rarely exemplified in everyday life.  Physics learning is only taught theoretically and has minimal explanation related to the implementation of Physics, so learning becomes less meaningful. Cultural or ethnoscientific approaches are important in implementing learning so that community culture is not lost. It can help improve students' scientific literacy and make science learning more meaningful for students. One of the technology-based learning media that can be developed is Physics educational games. This study aims to analyze the development needs of Physics educational games containing scientific literacy and ethnoscience. This type of research is descriptive quantitative. This research data instrument uses observation sheets and questionnaires. Data collection techniques are carried out through methods: (1) observation and (2) questionnaires. The research technique used is the quantitative descriptive analysis technique. The study subjects were 42 grade X students of SMAN 1 Padang. The students are represented by three classes X at SMAN 1 Padang, grouped into high, medium and low-level classes. The results showed that using learning media increased student participation in learning and made it easier for students to understand the material. Linking Physics learning with the local culture can make Physics learning more meaningful and increase students' scientific literacy. These results illustrate the need to develop physics educational games based on scientific literacy and ethnoscience.